Bilberry pomace in rabbit nutrition: effects on growth performance, apparent digestibility, caecal traits, bacterial community and antioxidant status. (18th May 2018) - Dabbou, S.; Ferrocino, I.; Kovitvadhi, A.; Dabbou, S.; Bergagna, S.; Dezzuto, D.; Schiavone, A.; Cocolin, L.; Gai, F.; Santoro, V.; Gasco, L.
Abstract : Agricultural by-products could be used as alternative raw materials in rabbit nutrition as they have been found to be highly nutritious and low cost feeding sources. The aim of this study was to estimate the nutritive value and potential use of bilberry pomace (BP) for growing rabbits. A total of 144 Grimaud rabbits (35 days old) were allotted to four groups and fed with a diet containing increasing level of BP: BP0 (basal diet), BP5, BP10 and BP15 containing 0, 50, 100 and 150 g/kg respectively. Growth trial lasted 48 days; apparent digestibility was evaluated, starting at 46 days of age, over 4 consecutive days. The nutritive value of BP was measured using the mean digestibility of the experimental diets. At 83 days of age, rabbits were slaughtered: blood, and liver and kidney samples were collected in order to determine the blood parameters and the antioxidant enzyme activities of the tissues. Moreover, caecal content was sampled and gut microbiota assessed by means of amplicon-based high-throughput 16S rRNA sequencing and PCR-denaturing gradient gel electrophoresis. The digestible protein was estimated to 104 g/kg of DM while digestible energy to 9.44 MJ/kg DM for incorporation rate up to 150 g/kg. During the finishing period, average daily feed intake and feed conversion ratio showed linear response to BP increase ( P =0.008 and <0.001, respectively). During all the period, both parameters decreased linearly and quadratically with increasing BP inclusion levels ( P <0.001) up to 100 g/kg of BP. A significant effect of the antioxidant status was found in the kidneys and liver ( P <0.05) where the glutathione peroxidase activity increased as the BP increased. As far as gut microbiota is concerned, BP increased the relative abundance of the Clostridium, Oscillospira, Ruminococcus and Ruminococcaceae species which were clearly associated with the BP inclusion level. In conclusion, BP showed a potential use as an alternative protein and fibre sources for growing rabbits.